Genome-wide identification and analysis of expression patterns of the ABC1K gene family members in Medicago sativa - Chen, Zhengqiang; Chen, Fangqi; Qin, Yaxuan; Wang, Le; Jia, Ruifang; Zhao, Jun; Lin, Kejian; Zhang, Yuanyuan (Frontiers in Plant Science, 2024)
The ABC1K (activity of bc1 complex kinase) atypical protein kinase family regulates diverse physiological functions in plants, including the development, growth, and response of plants to various stress stimuli. However, to date, only a few members of the alfalfa (Medicago sativa) ABC1K gene family have been identified, which severely limits the exploration of the functional mechanism of alfalfa ABC1K. Here, we identified 22 ABC1K genes from the alfalfa genome and categorized them into four types on the basis of phylogenetic analysis results and gene structure. The physical and biochemical properties, chromosomal location, subcellular localization, cis-regulatory elements, and conserved motifs of these genes were then characterized. Transcript profiling analysis confirmed that MsABC1Ks were widely expressed in various alfalfa tissues, with tissue-specific expression. We also found that salt and drought conditions significantly regulated MsABC1K genes expression, thus indicating that MsABC1K genes perform critical functions in alfalfa’s response to abiotic stress. In summary, the findings of our study serve as an important basis to enhance stress resistance of alfalfa and provide valuable insights to better comprehend the functions of the MsABC1K gene family.